2016
DOI: 10.1080/00380768.2016.1165598
|View full text |Cite
|
Sign up to set email alerts
|

Function of the methanogenic community in mangrove soils as influenced by the chemical properties of the hydrosphere

Abstract: Coastal ecosystems represent a potential additional source of the greenhouse gas methane (CH 4) that has been insufficiently quantified. Thus, to understand the mechanisms controlling greenhouse gas emissions in these ecosystems, this study investigated CH 4 emissions from and the related microbial properties of mangrove soils. Soil and gas samples were collected from several plots at different distances from the seashore in Soc Trang and Ca Mau in Vietnam, and the Sundarbans in India. Soil samples were incuba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…The 12‐year invasion by S. alterniflora also significantly increased rates of acetoclastic and hydrogenotrophic methanogenesis, along with the abundance of acetoclastic and hydrogenotrophic methanogens, thus suggesting that both forms of methanogenesis were not completely inhibited by sulphate reducers with an increasing sulphate concentration. This result and interpretation are consistent with those of sulphate‐rich mangroves (Arai et al, ), estuarine and marine sediments (Sela‐Adler et al, ; Treude et al, ), and oilfield fluids (Lv et al, ). It has been suggested that the co‐existence of methanogenesis and sulphate reduction is possible on competitive substrates and is primarily controlled via organic C input levels (Egger et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…The 12‐year invasion by S. alterniflora also significantly increased rates of acetoclastic and hydrogenotrophic methanogenesis, along with the abundance of acetoclastic and hydrogenotrophic methanogens, thus suggesting that both forms of methanogenesis were not completely inhibited by sulphate reducers with an increasing sulphate concentration. This result and interpretation are consistent with those of sulphate‐rich mangroves (Arai et al, ), estuarine and marine sediments (Sela‐Adler et al, ; Treude et al, ), and oilfield fluids (Lv et al, ). It has been suggested that the co‐existence of methanogenesis and sulphate reduction is possible on competitive substrates and is primarily controlled via organic C input levels (Egger et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…Methylotrophic methanogens were able to outcompete SRB by virtue of excess substrate by which they maintained higher activity in the surface layer sediments; thus, it was reasonable that phytate phosphorus would not affect methane production to a great extent. In contrast to the surface layer sediments, the bottom layer sediments lack some essential substances for microbial life in Arai et al (2016) , so methylotrophic methanogens may not be unfavored for methane production with increasing sediment depths ( Lee et al, 2015 ). However, when phytate phosphorus was added to the bottom layer sediments, methane production rate was significantly increased, meaning that OP may be a source of phosphorus rather than the substrate for methanogens in deeper sediments ( Broman et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported a significant amount of CH 4 flux from mangrove sediment [42][43][44][45][46][47][48][49] and have claimed that the contribution of CH 4 flux to global warming was non-negligible in estuarine mangrove forests, which could account for 18% to 22% of blue C burial rates [13] and 9% to 33% of plant CO 2 sequestration [50]. However, observed CH4 flux from mangrove soils is mostly negligible compared to CO 2 emissions from sediment but is highly variable [38][39][40][41][51][52][53][54][55][56][57][58], particularly for non-polluted mangrove sediment [21,49,[59][60][61][62]. To confirm this observation, the authors compared incubation experiments with mangrove sediment collected from the Vietnamese Mekong delta and the Indian Sundarbans forest [39].…”
Section: Significance Of Methane Emission From Mangrove Forestsmentioning
confidence: 99%
“…The gas species has become the second most important greenhouse gas in the atmosphere, contributing approximately 20% to global warming since the pre-industrial era [38]. The risk of further methane emission is due to mangrove sediment exposed to the above-mentioned anthropogenic impacts by stimulating related methanogens (i.e., CH 4 -producing microorganisms) and/or by inhibiting methanotroph (i.e., CH 4 -oxidizing microorganisms that contribute to lower the emission from the ecosystem) activity [39][40][41].…”
Section: Introductionmentioning
confidence: 99%